INTERAKSI VARIETAS KEDELAI DAN SAAT PEMBERIAN CEKAMAN KEKERINGAN PADA PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine Max. (L.) Merril) - Claudia Juniar Monggesang; Wenny ., Tilaar; Arthur G. Pinaria (Sam Ratulangi University, 2021)
This study aims to determine the interaction of varieties and drought stress on the growth and yield of two varieties of soybean (Glycine max (L.) Merill). This research was carried out using polybags in the greenhouse of the Faculty of Agriculture, Sam Ratulangi University with the experimental design used in this study was environmental design and treatment design was Completely Randomized Design (CRD). Research data from all observational variables were analyzed by analysis of variance ANOVA and if there was a difference between treatments, it was continued with the 5% BNT test. The results of this study indicate that the character of soybean harvesting age is influenced by the interaction of varietal factors and drought stress factors. Drought stress factors affect the character of plant height, number of main branch books, number of pods planted, and number of seeds planted. Varieties and drought stress factors did not affect the observed characteristics of the first flowering age, the number of root nodules, the number of empty pods, and the weight of 100 seeds per plant.